Attitudes towards Motivation in Mathematics: A Case Study on Engineering Technology Students at FTK, UTeM - Kashi'ie, Najiyah Safwa; Hamzah, Khairum; Waini, Iskandar; Salim, Fadzilah; Mukhtar, Mohd Fariduddin; Zainal, Nurul Amira (2014)
The aims of this study were to understand and examine the Engineering Technology (ET) students’ attitudes towards their motivation while learning mathematics during their studies at the Faculty of Engineering Technology (FTK), Universiti Teknikal Malaysia Melaka (UTeM). In this study, a set of questionnaire from a previous study by Galbraith and Haines (1998) was utilized, which included questions on the students’ attitudes towards their motivation while learning mathematics. A total of 332 second year ET students at FTK, UTeM were requested to complete the questionnaire during the final week of semester two of the 2013/2014 session. From the findings, a conclusion was drawn regarding the ET students’ attitudes towards motivation while learning mathematics. The result showed that most ET students had positive attitudes towards their motivation while learning mathematics during their studies at FTK, UTeM.